Editorial - Maria Frahm-Arp (Journal for the Study of Religion)
The Pentecostal movement has since its inception been a dynamic movement in which the theology, practice, and expressions of faith have shifted. This is primarily, but not solely, due to four central factors. First, it is a movement and not a centralized organization, meaning that there is no central authority that governs how it develops, when and how new congregations or churches are formed, and how these evolve. As a movement, it is a loose collection of churches and groups, some of which do not specifically self-identify as Pentecostal, but are categorized by academics as Pentecostal due to their theology and/or practices. The article by Podolecka and Cheyeka explores this reality in Zambia where some churches consider themselves Pentecostal while other Pentecostals do not recognize these churches as part of the movement. In a different vein, Aidoo examines the phenomena of cursing prayers in which pastors criticize each other and claim other pastors as not being Christians in their prayers. Second, there is no centralized canonical theology determined by a particular body or group with authority to establish and enforce rules or regulations, meaning that the groups and churches in the movement are free to development their own theologies. The article by Resane explores this idea as he examines the impact of the Shepherding Movement within Pentecostalism and how a group of five men in the USA established a model for how churches should be run, but the movement was problematic and fell apart in the 1990s.